TYPE 2 DIABETES MELLITUS AND CARDIOVASCULAR COMPLICATIONS: PATHOPHYSIOLOGICAL LINKS AND MODERN THERAPEUTIC STRATEGIES (International journal of medical sciences, 2026)
Type 2 Diabetes Mellitus (T2DM) is a chronic metabolic disorder defined by insulin resistance, progressive pancreatic beta-cell dysfunction, and persistent hyperglycemia. Cardiovascular disease represents the leading cause of morbidity and mortality among diabetic patients, driven by complex metabolic, inflammatory, and vascular mechanisms. Chronic hyperglycemia induces endothelial dysfunction, oxidative stress, and dyslipidemia, which accelerate atherosclerosis and microvascular injury. Modern therapeutic approaches emphasize not only glycemic control but also cardiovascular risk reduction through pharmacological interventions including SGLT2 inhibitors, GLP-1 receptor agonists, statins, and antihypertensives, complemented by lifestyle modification. This article provides a comprehensive overview of the pathophysiological links between T2DM and cardiovascular disease, clinical manifestations, diagnostic approaches, and contemporary evidence-based management strategies aimed at improving long-term outcomes.